2015
DOI: 10.1108/jfep-03-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio investment outflow and the complementary role of direct investment

Abstract: Purpose – This paper aims to uncover potential contemporaneous relationship between foreign portfolio investment (FPI) and another popular type of cross-border investment outflow, namely, foreign direct investment (FDI). Design/methodology/approach – The relationship between FPI and FDI are modeled using simultaneous equations approach to take potential endogeneity in to account. In a panel of 45 countries over the period of 2001-2009, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
1
8
2
Order By: Relevance
“…This finding was also in line with previous results from the FDI mean group output and the subsequent conclusion that, given the state of institutional quality, the two investment inflows could have been substitutes in this sample of emerging markets. These results contradict those of Noman et al (2015), who found a positive link between FDI and FPI, with FPI having a greater impact on FDI in a sample of 45 developed and developing countries. Noman et al (2015) did not take into account the effect of institutions, however, but only that of variables such as differentials in market openness, exchange rates and inflation rates.…”
Section: Cointegration and Error Correction Model Results With Fpi As The Dependent Variable-dynamic Fixed Effectscontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding was also in line with previous results from the FDI mean group output and the subsequent conclusion that, given the state of institutional quality, the two investment inflows could have been substitutes in this sample of emerging markets. These results contradict those of Noman et al (2015), who found a positive link between FDI and FPI, with FPI having a greater impact on FDI in a sample of 45 developed and developing countries. Noman et al (2015) did not take into account the effect of institutions, however, but only that of variables such as differentials in market openness, exchange rates and inflation rates.…”
Section: Cointegration and Error Correction Model Results With Fpi As The Dependent Variable-dynamic Fixed Effectscontrasting
confidence: 99%
“…These results contradict those of Noman et al (2015), who found a positive link between FDI and FPI, with FPI having a greater impact on FDI in a sample of 45 developed and developing countries. Noman et al (2015) did not take into account the effect of institutions, however, but only that of variables such as differentials in market openness, exchange rates and inflation rates.…”
Section: Cointegration and Error Correction Model Results With Fpi As The Dependent Variable-dynamic Fixed Effectscontrasting
confidence: 99%
“…Moreover, the FDI results revealed a statistically significant but negative association between FPI inflows and FDI inflows. Although this result contrasted the complementary and positive association found by Noman, Rahman and Naka (2015); it, however, corroborated the findings of Humanicki, Kelm and Olszewski (2017) of a trade-off or substitutability relationship between FDI and FPI inflows, in the case of Poland.…”
Section: Results and Discussion Of Findingssupporting
confidence: 86%
“…Generally speaking, the growth rates of the developed countries are slower than the emerging ones, which attract more amounts of flows from overseas to take advantage of this differential. Nevertheless, given the fact that economies follow different cycle, investors prefer to invest in the less risky financial markets (Noman et al, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%